A company in transition: Fiat Mirafiori of Turin. (16th July 2008) - Garibaldo, Francesco
In the last three years, FIAT AUTO recovered from a quasi-desperate financial situation and had started a new managerial pattern affording through an overall plan for business reorganisation ranging from the products to the productive process. The intervention in the productive process and thus, the organisational model, has had direct repercussions on the working conditions, which is the aspect this paper will be dealing with, referring exclusively to the Mirafiori plant in Turin. The paper will comment on the outcomes of a very recent survey organised by one of the members of the Metalworkers Union and will stress the very transitional sate of the workers' conditions up until now.